Faculty Development Structures and Activities in Ontario’s Colleges of Applied Arts and Technology - Jones, Glen A.; Geis, George L. (Canadian Journal of Higher Education, 1995)
The paper presents a discussion of faculty development in 22 of Ontario's Colleges of Applied Arts and Technology. We report the findings of a survey which collected information on administrative structure, funding, mandate, faculty development activities, publication, incentives for faculty participation, assessment of faculty needs and evaluation. We conclude by raising a number of questions which faculty developers might address as changes in the social, political and economic environment present new challenges to colleges and universities.